ANALISIS KEPUTUSAN KONSUMEN MEMBELI SEPEDA DI MASA PANDEMI COVID-19 BERDASARKAN GAYA HIDUP, CITRA MEREK, DAN SOCIAL INFLUENCE - Albiyansyah, Dafa (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2026)
This study aims to determine the effect of Lifestyle, Brand Image, and Social Influence on Consumer Purchase Decisions for Bicycles in the Pandemic Period. The respondents in this study were the people of DKI Jakarta who bought bicycles during the pandemic, the number of which was unknown. The sampling technique used was the population in this study as many as 155 respondents. The sample in the study amounted to 155 people from DKI Jakarta who bought bicycles during the pandemic. The data analysis method used is Partial Least Square technical using the SmartPLS statistical software, with the research instrument being a questionnaire. The results of this study indicate that Lifestyle and Brand Image have a significant effect, while Social Influence has no significant effect on Purchase Decisions.